PENGARUH KOMBINASI SUPLEMENTASI VITAMIN C DAN VITAMIN E SINTETIS TERHADAP PRODUKSI DAN DAYA TETAS TELUR PUYUH EFFECT OF COMBINATION BETWEEN VITAMINE C AND VITAMINE E SYNTHETIC SUPPLEMENTED TO PRODUCTION AND EGG HATCHABILITY OF QUAIL - Subekti, Endah (MEDIAGRO, 2005)
The experiment was conducted to determine the effect of vitamine C and vitamine E supplementation in quail diet on production, and egg hatchability. Two hundred and fourty three of female quails of one month old and eighty one of male quails of two month old were devided into nine dietary treatments. Each treatments was replicated three times with nine female quails and three male quails per replication. The nine dietary treatments were there of R0 (diet with CP 21 % and ME 2600 kcal/kg), R1 (R0 +  150 mg/kg vitamine C ), R2 (R0 + 300 mg/kg vitamine C), R3 ( R0 + 25 I.U/kg vitamine E ), R4 ( R0 + 50 I.U/kg vitamine E ), R5 ( R0 +  150mg/kg vitamine C + 25 I.U/kg vitamine E ), R6 ( R0 + 150 mg/kg vitamine C + E 50 I.U/kg vitamine E ), R7 ( R0 + 300 mg/kg vitamine C + 25 I.U/kg vitamine E ), R8 ( R0 + 300 mg/kg vitamine C + 50 I.U/kg vitamine E ). All dietary treatments and drinking water were given adlibitum. The measured variables were feed consumption, eggs production,  fertility, and hatchability. The collected data were analysed using analysis of variance following a Completely Randomized Design and continued by Contrast Test if the result indicated significant differences. The result showed that vitamine C supplementation in quail diet was very significantly (P<0.01) increased feed consumption and eggs production. It showed significantly (P<0.05) increase on fertility and hatchability.Vitamine E supplementation in quail diet caused very significant (P<0.01) increase on fertility, hatchability, but it did not significantly increase feed consumption and eggs production. Combination between vitamine C and vitamine E supplementation in quail diet caused very significant (P<0.01) increase on feed  consumption, eggs production,  fertility and hatchability. Diet combination between 300 mg/kg vitamine C and 50 IU/kg vitamine E (R8) resulted the best eggs production and hatchabilityof quail.Key word : Quail, Vitamine  C, Vitamine E, Production, Hatchability